2020
DOI: 10.4018/978-1-7998-2503-6.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging Practices in Early Childhood Classrooms From an Intercultural Perspective

Abstract: The term ‘translanguaging' not only has appeared in the field of Applied Linguistics, but also it entered in the field of Multilingual/Multicultural Education in early childhood classrooms. Translanguaging is mostly seen as an opportunity to build on emergent bilingual speakers' full language repertoires in order to scaffold language learning; however, it also provides an opportunity for young learners to gain cross-cultural knowledge. The authors observed translanguaging practices during play time in the AraN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Hence, intercultural awareness was raised to a higher level through these innovative practices. These findings are consistent with those of Csillik and Golubeva (2019), who applied translanguaging practices at a preschool in the USA and observed that the young learners gained cross-cultural knowledge and developed intercultural awareness through playful activities and emerging students' linguistic repertoires.…”
Section: Discussion Of the 3 Rd Research Questionsupporting
confidence: 90%
“…Hence, intercultural awareness was raised to a higher level through these innovative practices. These findings are consistent with those of Csillik and Golubeva (2019), who applied translanguaging practices at a preschool in the USA and observed that the young learners gained cross-cultural knowledge and developed intercultural awareness through playful activities and emerging students' linguistic repertoires.…”
Section: Discussion Of the 3 Rd Research Questionsupporting
confidence: 90%
“…Besides its contribution to increased academic success, pedagogical translanguaging has proven helpful in supporting learners' emotional wellbeing as it mitigates the negative emotions (e.g., anxiety, fear, frustration, and apprehension) often associated with monolingual instruction (Back et al, 2020). On a more socio-cultural level, translanguaging has also been shown to be valuable in raising learners' critical understanding of language and culture and consequently nurturing positive attitudes and tolerance towards linguistic and cultural diversity among them (Csillik & Golubeva, 2020).…”
Section: Potential Of Translanguaging In Tesolmentioning
confidence: 99%
“…In the Greek educational setting, there has been a shift from focusing solely on teaching Greek to indigenous/immigrant/refugee children, to a This study has also yielded significant insights regarding the role of translanguaging in enhancing intercultural communication. It has become evident that an environment encouraging translanguaging and the use of the entire linguistic range of each child significantly boosts their intercultural sensitivity and awareness of others (Ou et al, 2023;Csillik & Golubeva, 2020;Wells, 2018). The observation notes and the children's responses revealed a heightened motivation to engage with and learn about different cultures and languages.…”
Section: Figure 10 Translanguaging and Emotions 1/2mentioning
confidence: 99%